From Theory to Practice: The Application of Cognitive Load Theory to the Practice of Medicine. (January 2021) - Szulewski, Adam; Howes, Daniel; van Merriënboer, Jeroen J.G.; Sweller, John
Abstract : Cognitive load theory has become a leading model in educational psychology and has started to gain traction in the medical education community over the last decade. The theory is rooted in our current understanding of human cognitive architecture in which an individual's limited working memory and unlimited long-term memory interact during the process of learning. Though initially described as primarily a theory of learning, parallels between cognitive load theory and broader aspects of medical education as well as clinical practice are now becoming clear. These parallels are particularly relevant and evident in complex clinical environments, like resuscitation medicine. The authors have built on these connections to develop a recontextualized version of cognitive load theory that applies to complex professional domains and in which the connections between the theory and clinical practice are made explicit, with resuscitation medicine as a case study. Implications of the new model for medical education are also presented along with suggested applications.